2006
DOI: 10.1124/jpet.105.097931
|View full text |Cite
|
Sign up to set email alerts
|

Verapamil P-glycoprotein Transport across the Rat Blood-Brain Barrier: Cyclosporine, a Concentration Inhibition Analysis, and Comparison with Human Data

Abstract: To predict the magnitude of P-glycoprotein (P-gp)-based drug interactions at the human blood-brain barrier (BBB), rodent studies are routinely conducted where P-gp is chemically inhibited. For such studies to be predictive of interactions at the human BBB, the plasma concentration of the P-gp inhibitor must be comparable with that observed in the clinic. Therefore, we determined the in vivo EC 50 of P-gp inhibition at the rat BBB using verapamil as a model P-gp substrate and cyclosporine A (CsA) as the model P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
90
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 19 publications
9
90
6
Order By: Relevance
“…Using daunorubicin, digoxin, and cyclosporine A as P-gp substrates, we observed that the IC 50 of quinidine and verapamil in human, monkey, canine, rat, and mouse P-gp-transfected cells could vary by 6-fold, although the majority of the IC 50 values are within 2-fold. In contrast, the K p of verapamil increased by 78% in rats and 75% in humans where plasma concentration of cyclosporine was 2.8 M, indicating no species difference for verapamil-cyclosporine DDI (Hsiao et al, 2006).…”
Section: Downloaded Frommentioning
confidence: 87%
“…Using daunorubicin, digoxin, and cyclosporine A as P-gp substrates, we observed that the IC 50 of quinidine and verapamil in human, monkey, canine, rat, and mouse P-gp-transfected cells could vary by 6-fold, although the majority of the IC 50 values are within 2-fold. In contrast, the K p of verapamil increased by 78% in rats and 75% in humans where plasma concentration of cyclosporine was 2.8 M, indicating no species difference for verapamil-cyclosporine DDI (Hsiao et al, 2006).…”
Section: Downloaded Frommentioning
confidence: 87%
“…11 C]verapamil in the human and rat brain after treatment with low doses of the potent in vivo P-gp inhibitor cyclosporin A (CsA), they did not observe any species differences (Hsiao et al, 2006). Other explanations could be species differences in blood-brain barrier transport that are not related to P-gp function, but rather to other causes, e.g., tightness of the endothelial cell tight junctions or expression of other active efflux transporters.…”
mentioning
confidence: 89%
“…In vivo evidence for species differences in P-gp function has so far only been reported by one group, who compared rats and guinea pigs and found that higher concentrations of the P-gp inhibitor GF-120918 were needed in guinea pigs than in rats to achieve the same increase in brain concentrations of an undisclosed P-gp substrate (Cutler et al, 2006). In contrast, when Hsiao et al (2006) compared the increase of […”
mentioning
confidence: 91%
“…Since previously reported P-gp humanized mice did not express functional P-gp at the BBB (Sadiq et al, 2015), the hMDR1-MAC mouse is the first P-gp humanized mouse model expressing functional P-gp in brain capillaries. Furthermore, the mice may be valuable for predicting P-gpmediated drug-drug interactions at the BBB, although the effect of a P-gp inhibitor on the brain distribution of drugs is limited in a clinical setting (Sasongko et al, 2005;Hsiao et al, 2006;Muzi et al, 2009;Wagner et al, 2009;Bauer et al, 2015).…”
Section: Discussionmentioning
confidence: 99%